Predictors of social identity on the national-European dimension - Franceško Mirjana (Sociologija, 2006)
This paper analyzes socio-demographic and psychological predictors of European identity in Serbia and Montenegro. The research conducted in 2003 was based on the sample of 2860 respondents from four regions of Serbia and Montenegro. The respondent of both sexes were included in the sample, aged 18 to 43 with different education. Battery of questions comprising psychological variables was mainly developed at University of Novi Sad (Department of Psychology). The following variables were taken as psychological predictors: motivations (of general achievement, tested with MOP2002 scale; and locus of control, tested with LOK2003 scale), value orientations (conservatism-radicalism, tested with KORA2002 scale; and individualism-collectivism, tested with KOIN2002 scale), and personal characteristic of rigidity tested with RG-s scale. The effects of other socio-demographic characteristics (age and education) also were tested. Employed multiple regression (stepwise forward) proved that: sexual conservatism, rigidity as a need for detailed planning, individualism-collectivism, some components of achievement motive (orientation towards planning and aim as a source of satisfaction), age and education, have relatively stable predictive value of social identity on national-European dimension. Predictive value of external locus of control and other dimensions of achievement motive is limited and depends on a rang of other personal characteristics.